2004
DOI: 10.1007/s00213-003-1745-y
|View full text |Cite
|
Sign up to set email alerts
|

Effects of corticosterone on place conditioning to ethanol

Abstract: The effects of corticosterone on ethanol-induced place conditioning are substantially affected by the conditioning schedule used.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 24 publications
1
7
0
Order By: Relevance
“…The current finding is, however, inconsistent with other data that indicate that acute CORT administration does affect ethanol-induced conditioned place preference. Brooks et al (2004) observed that acute administration of 10 mg/kg CORT to mice attenuated ethanol-induced conditioned place preference when using the conventional, alternate day, place conditioning schedule but potentiated ethanolinduced conditioned place preference when using a rapid, same day, conditioning schedule. While the conventional conditioning procedure exposes the animal to only one conditioning session per day and alternates between drug and control sessions, the rapid schedule subjects the animal to a control conditioning session immediately followed by a drug session each day.…”
Section: Effects Of Cort On Licl-induced Conditioned Place Aversionmentioning
confidence: 95%
See 1 more Smart Citation
“…The current finding is, however, inconsistent with other data that indicate that acute CORT administration does affect ethanol-induced conditioned place preference. Brooks et al (2004) observed that acute administration of 10 mg/kg CORT to mice attenuated ethanol-induced conditioned place preference when using the conventional, alternate day, place conditioning schedule but potentiated ethanolinduced conditioned place preference when using a rapid, same day, conditioning schedule. While the conventional conditioning procedure exposes the animal to only one conditioning session per day and alternates between drug and control sessions, the rapid schedule subjects the animal to a control conditioning session immediately followed by a drug session each day.…”
Section: Effects Of Cort On Licl-induced Conditioned Place Aversionmentioning
confidence: 95%
“…This result is consistent with other research suggesting that CORT may not induce a significant conditioned place aversion. For example, administration of 10 mg/kg CORT did not produce any significant place conditioning effects (Brooks et al, 2004). Moreover, CORT administration did not produce a conditioned taste aversion when paired with a novel flavour (Kent et al, 2000(Kent et al, , 2002.…”
Section: Cort-induced Conditioned Place Aversionmentioning
confidence: 99%
“…It was reported that ethanol (0.7 and 1.5 g/kg ig) produced robust CPA, regardless of whether the rats were ethanol‐naïve or whether they had received ig ethanol (1.5 g/kg) for 15 days prior to conditioning, and regardless of whether ethanol (1 g/kg ig) was infused over 30 seconds or over 600 seconds before the conditioning sessions. Brooks et al . (2004) found ethanol‐induced CPP in mice at 2 and 2.5 g/kg ip, but not at 1.5 g/kg ip, when ethanol and vehicle conditioning were conducted on alternating days.…”
Section: Studies Using Systemic Drug Treatmentsmentioning
confidence: 99%
“…(2006). Brooks et al . (2004) found ethanol‐induced CPP in mice at 2 and 2.5 g/kg ip, but not at 1.5 g/kg ip, when ethanol and vehicle conditioning were conducted on alternating days.…”
Section: Studies Using Systemic Drug Treatmentsmentioning
confidence: 99%
“…at doses of 2.5 mg/kg and 5 mg/kg in a volume of 1 ml/kg. Doses were chosen on the basis of previous studies (Brooks et al, 2004; Graf et al, 2013). …”
Section: Methodsmentioning
confidence: 99%